Barriers and facilitators of healthcare access for long COVID-19 patients in a universal healthcare system: qualitative evidence from Austria - Gamillscheg, P; Łaszewska, A; Kirchner, S; Hoffmann, K; Simon, J; Mayer, S (BioMed Central, 2024)
Background: Long COVID-19 challenges health and social systems globally. International research finds major inequalities in prevalence and healthcare utilization as patients describe difficulties with accessing health care. In order to improve long-term outcomes it is vital to understand any underlying access barriers, for which relevant evidence on long COVID-19 is thus far lacking in a universal healthcare system like Austria. This study aims to comprehensively identify access barriers and facilitators faced by long COVID-19 patients in Austria and explore potential socioeconomic and demographic drivers in health and social care access. Methods: Applying an exploratory qualitative approach, we conducted semi-structured interviews with 15 experts including medical professionals and senior health officials as well as focus groups with 18 patients with confirmed long COVID-19 diagnosis reflecting varying participant characteristics (age, gender, urbanicity, occupation, education, insurance status) (July-Nov 2023). Data were analysed following a thematic framework approach, drawing on a comprehensive ‘access to health care’ model. Results: Based on expert and patient experiences, several access barriers and facilitators emerged along all dimensions of the model. Main themes included scepticism and stigma by medical professionals, difficulties in finding knowledgeable doctors, limited specialist capacities in the ambulatory care sector, long waiting times for specialist care, and limited statutory health insurance coverage of treatments resulting in high out-of-pocket payments. Patients experienced constant self-organization of their patient pathway as stressful, emphasizing the need for multidisciplinary care and centralized coordination. Facilitators included supportive social environments, telemedicine, and informal information provided by a nationwide patient-led support group. Differences in patient experiences emerged, among others, as women and younger patients faced gender- and age-based stigmatization. Complementary health insurance reduced the financial strain, however, did not ease capacity constraints, which were particularly challenging for those living in rural areas. Conclusions: The findings of this study indicate a call for action to improve the long COVID-19 situation in Austria by empowering both providers and patients via increased information offerings, strengthened interdisciplinary treatment structures and telemedicine offerings as well as research funding. Our insights on potentially relevant socioeconomic and demographic drivers in access barriers lay the necessary foundation for future quantitative inequality research.